Labour market integration of people with intellectual disabilities - Martín-del-Río , Beatriz; Sánchez Sánchez , Beatriz; García Selva , Adrian; Pons Ferrández , Inmaculada; Solanes-Puchol , Ángel (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Introduction. In recent years, attention to diversity has been gaining relevance as a study phenomenon. The need for the inclusion of people with disabilities of working age in the labour market is becoming more and more evident. In recent years, both educational and legislative measures have been implemented. At the legislative level in Spain it is established that, in the public administration, 7% of the total number of vacancies offered must be reserved for people with disabilities. Of these places, 2% of the positions must be reserved for people with intellectual disabilities (Royal Legislative Decree 5/2015). This measure is in line with the advancement of the intention of integration. This review aims to provide information on how the international scientific literature is addressing the issue, by analysing the literature and using bibliometric methodology, in order to reveal the characteristics and the path it is following. Methodology. The database analysed, the Web of Science (WOS), includes 257 articles that have been published in different scientific journals. The following bibliometric indicators were analysed: temporal distribution, author productivity, most productive authors according to Cole and Cole's classification (1973), invisible college or collaborative network of the most productive author (Crane, 1969), citations received, journal productivity, most productive journals according to Bradford's Law (1934), and content analysis of the papers. Results: The results show a recent study of the subject starting in 2000, as well as a growth in the number of publications in recent years. Of the 730 authors who have signed papers, 76.76% have signed only one paper and only two are major producers with more than 10 papers publishing from Australia and Spain. In general, these papers have not been highly cited, with only two papers standing out with more than 100 citations. In terms of journals, 98 have published these papers, with three standing out as the most productive: the Journal of Applied Research in Intellectual Disabilities, the Journal of Intellectual Disability Research, and the Journal of Intellectual & Developmental Disability. Finally, the content analysis carried out on the descriptor terms with a significant frequency of appearance shows the areas of study and variables on which the research has focused most, with a higher representation of variables related to the psychological and occupational fields.